REMOTE SENSING OF LAND SURFACE TEMPERATURE USING LANDSAT TM THERMAL INFRARED BAND - Asmala, A.; Noorazuan, H. (Universiti Teknologi Malaysia, 2006)
A full-scene of Landsat TM data acquired on April 17, 1988 (path 127/row 58) was used in this study. The scene covers the area of Selangor and North part of Negeri Sembilan in Peninsular Malaysia. The main objective of this study is to evaluate the use of remote sensed information, especially thermal band 6 to gain land surface temperature (LST) using thermal band of Landsta images. The result will be compared with urban and non-urban surfaces by using normalised difference vegetation index (NDVI) and the relationship between them will be analysed. The initial result showed that the correlation between the LST and NDVI over ten locations in the study area is quite significant. The derivation of LST map using remote sensing technique in this study is useful in providing information for analysing geophysical parameters over Selangor-Negeri Sembilan area, especially dealing with urban and heat island phenomenon.